Diagnostic accuracy of sonoelastography in different diseases - Iqra Manzoor; Raham Bacha; Syed Amir Gilani (Journal of Ultrasonography, 2018)
The objective of this study was to evaluate the diagnostic accuracy of sonoelastography in patients of primary and secondary health care settings. Google scholar, PubMed, Medline, Medscape, Wikipedia and NCBI were searched in October 2017 for all original studies and review articles to identify the relevant material. Two reviewers independently selected articles for evaluation of the diagnostic accuracy of sonoelastography in different diseases based on titles and abstracts retrieved by the literature search. The accuracy of sonoelastography in different diseases was used as the index text, while B-mode sonography, micro pure imaging, surgery and histological findings were used as reference texts. Superficial lymph nodes, neck nodules, malignancy in thyroid nodules, benign and malignant cervical lymph nodes, thyroid nodules, prostate carcinoma, benign and malignant breast abnormalities, liver diseases, parotid and salivary gland masses, pancreatic masses, musculoskeletal diseases and renal disorders were target conditions. The data extracted by the two reviewers concerning selected study characteristics and results were presented in tables and figures. In total, 46 studies were found for breast masses, lymph nodes, prostate carcinoma, liver diseases, salivary and parotid gland diseases, pancreatic masses, musculoskeletal diseases and renal diseases, and the overall sensitivity of sonoelastography in diagnosing all these diseases was 83.14% while specificity was 81.41%. This literature review demonstrates that sonoelastography is characterized by high sensitivity and specificity in diagnosing different disorders of the body.